2001
DOI: 10.1073/pnas.141124698
|View full text |Cite
|
Sign up to set email alerts
|

Guanylyl cyclase C agonists regulate progression through the cell cycle of human colon carcinoma cells

Abstract: The effects of Escherichia coli heat-stable enterotoxin (ST) and uroguanylin were examined on the proliferation of T84 and Caco2 human colon carcinoma cells that express guanylyl cyclase C (GC-C) and SW480 human colon carcinoma cells that do not express this receptor. ST

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
205
2
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(215 citation statements)
references
References 44 publications
(41 reference statements)
6
205
2
2
Order By: Relevance
“…In addition, proliferation of glomerular mesangial cells by phorbol 12,13-dibutyrate-mediated activation of mitogen-activated protein kinase is antagonized by cGMPinduced expression of the specific phosphatase MKP-1 (27). Further, in colorectal cancer cells, the antiproliferative effects of cGMP may reflect activation of apoptotic pathways (28,29) or regulation of cell cycle (15). Conversely, cGMP-dependent activation of PKG promotes human umbilical vein endothelial cell proliferation by stimulating Raf-1 kinase activity (30).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, proliferation of glomerular mesangial cells by phorbol 12,13-dibutyrate-mediated activation of mitogen-activated protein kinase is antagonized by cGMPinduced expression of the specific phosphatase MKP-1 (27). Further, in colorectal cancer cells, the antiproliferative effects of cGMP may reflect activation of apoptotic pathways (28,29) or regulation of cell cycle (15). Conversely, cGMP-dependent activation of PKG promotes human umbilical vein endothelial cell proliferation by stimulating Raf-1 kinase activity (30).…”
Section: Resultsmentioning
confidence: 99%
“…The precise mode of Ca 2ϩ delivery to its intracellular site of action to induce intestinal cell cytostasis remains undefined. Yet, this antiproliferative process must be tightly regulated because Ca 2ϩ can, upon intracellular accumulation, promote apoptosis (42), which is not induced by ST (15).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Addition of exogenous uroguanylin 1 or guanylin, 4 mammalian ligands of GC-C, causes apoptosis in confluent T84 cells. A third study 5 showed that serum-stimulated proliferation was inhibited by ST or uroguanylin via a delay in cell cycle progression in the absence of apoptosis. It has recently been shown that ST exposure activates calcium influx through cyclic nucleotide-gated channels in rat colonocytes 6 and in T84 cells, where it is associated with decreased proliferation.…”
mentioning
confidence: 99%